FAKTORâFAKTOR YANG MEMPENGARUHI PERUSAHAAN MEMBUTUHKAN JASA KANTOR AKUNTAN PUBLIK (Studi Empiris Pada Perusahaan Menengah Di Kota Medan) - Silalahi, Sem Paulus (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
The study was conducted using a survey method being medium-sized in MedanCity. The study aimed to determine whether the factors of financial reporting fraud,bank loan application, determination of the tax burden, and perceived needs ofenterprise organization is a factor of the service public accounting firm (KAP).Thepopulation in the study is a mediumâsized enterprise in Medan City. Samples takenamounted to 23 medium-sized enterprise in Medan City with 63 respondents. Typesof data used are primary data by the method of data collection using questionnaires.The method of data analysis used in this study is multiple regression with the help ofsoftware SPSS version 17.00. The results showed that the factor of fraudulentfinancial reporting, bank credit application, the determination of the tax burden, andsignificant effect on variabel y, which is the perception of organizations requireenterprise service public accounting firm (KAP). With a significance value of eachvariable is equal to 0.000 at an alpha level of 0.05 (5%). Adjusted R Square value isequal to 0.979, showed that 97.9% of the independent variable in this study is ableto influence the dependent variable, while 2.1% is influenced by other variablesoutside of research.Keywords : Company requires service public accounting firm, financial reportingfraud, bank credit application, determination of tax expense,organizational perception